FEASIBILITY STUDY OF FOOD WASTE RECYCLING BUSINESS UTILIZING TTT ENZYME-BASED TECHNOLOGY - Zenu Djohan; Soebiakto Sukarno (CV. Radja Publika, 2025)
Driven by rapid urbanization and population growth, Indonesia is still struggling with food waste management, which raises major environmental, social and economic concerns. Conventional waste disposal methods such as landfilling and open dumping have exacerbated soil contamination, health risks and greenhouse gas emissions, therefore stressing the immediate need for more sustainable solutions. This study evaluates the feasibility of establishing a food waste recycling business utilizing TTT enzyme-based technology, which converts food waste into organic compost fertilizers within merely three hours – allowing significant improvement over traditional composting methods that typically require weeks or months. The research adopts a mixed methods and approaches, combining quantitative data collected from surveys targeting Jabodetabek and Bandung residents with qualitative data gathered from literature reviews and expert interviews. Key findings show that TTT enzyme-based technology promotes sustainable agriculture and support circular economy by offering faster processing, lower costs and greener environmental impact. Financial analysis results in strong viability and investment attractiveness, with a projected annual revenue of IDR 108.5 billion and a net profit margin of 27.66%. This study concludes that TTT enzyme-based technology has the potentials to transform food waste management in Indonesia, therefore fostering environmental sustainability and economic resilience throughout the nation.